Assessment of SCoT and ISSR molecular markers in genetic diversity of rigid ryegrass (Lolium rigidum Gaud.) in Iran - Keshavarzi, Maryam; Tabaripour, Raheleh; Ullah, Fazal (Phytotaxa, 2022)
Lolium rigidum (Poaceae) is important forage and weed species grown in different habitats of Iran. Rigid ryegrass originated from the Mediterranean region. They are very resistant to common herbicides. To investigate the genetic variability of L. rigidum, we studied 81 individuals of 18 natural populations from Iran; four ISSR and four SCoT primers were used. These are reproducible and highly polymorphic markers. We examined their gene flow and genetic variation. Genetic diversity among and within populations was determined through different methods. The Mantel test indicated a significant correlation between these populations’ genetic distance and geographical distance and a high correlation between ISSR and SCoT markers. Analyses of molecular variance (AMOVA) produced high genetic differences among the studied populations for both markers. Structure analysis showed population genetic stratification and identified three genetic groups through ISSR molecular markers for L. rigidum in Iran and indicated restricted gene flow. The current investigation revealed the productivity of ISSR and SCoT molecular markers in evaluating genetic variation and grouping of wild populations of L. rigidum and provides detailed data concerning the genetic structure of its populations. The present finding provided useful information for further conservation, selection, and breeding plans.